Numerical Study of Reactive Flow in Fractured Carbonate Rock - Zhou, Xu; Zhang, Qingfu; Xing, Hongchuan; Lv, Jianrong; Su, Haibin; Huang, Zhaoqin (Frontiers in Earth Science, 2021)
Acidizing technology is an effective reformation method of oil and gas reservoirs. It can also remove the reservoir pollution near wellbore zones and enhance the fluid transmissibility. The optimal injection rate of acid is one of the key factors to reduce cost and improve the effect of acidizing. Therefore, the key issue is to find the optimal injection rate during acid corrosion in fractured carbonate rock. In this work, a novel reactive flow mathematical model based on two-scale model and discrete fracture model is established for fractured carbonate reservoirs. The matrix and fracture are described by a two-scale model and a discrete fracture model, respectively. Firstly, the two-scale model for matrix is combined with the discrete fracture model. Then, an efficient numerical scheme based on the finite element method is implemented to solve the corresponding dimensionless equations. Finally, several important aspects, such as the influence of the injection rate of acid on the dissolution patterns, the influence of fracture aperture and fracture orientations on the dissolution structure, the breakthrough volume of injected acid, and the dynamic change of fracture aperture during acidizing, are analyzed. The numerical simulation results show that there is an optimal injection rate in fractured carbonate rock. However, the fractures do not have an impact on the optimal acid injection rate, they only have an impact on the dissolution structure.